Moderate doses of caffeine improve intermittent exercise performance and executive function in female team athletes in high-temperature and humidity environments - Quan, L.; Wen, W.; Fan, H. (Science & Sports, 2025)
Purpose This study aimed to investigate the effects of different doses of caffeine intake on intermittent exercise performance and executive function in female basketball players in high-temperature and humidity environments.